THE MOTIVATIONS OF FARMER (RICE) TO CHANGED WITH GADING COCONUT ON SIMALIDU KOTO SALAK DHARMASRAYA - Yulirman, Yulirman; Suarto, Edi; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
The aims of this research is to got information, to analize, and to describing data about motivation of changes farmer (rice) to progres gading coconut on simalidu koto salak dharmasraya can see from : 1) because of the less rice production so the farmer have motivations to changes to progress gading coconut. 2) the high gading coconut prices so the farmer have motivations to progress gading coconut. 3) also, because the farmer more easy to organize it. The kids of the qualitative research with using interview tehnique. Beause the problems solving the researcher use sekunder of data and primer of data to answer og the questions. The primer of data collected by observation, interview, discussion process informant, and take of images on the outside area, than of sekunder got from informant people apropriate with his/her specialist. The result of this research explains that 1) less of rie production, so the farmer have motivations to cange with gading coconut on simalidu koto salak damasraya the public perfoman beause goose farmer cange wet rice field land became to progress gading coconut. 2) the high gading coconut prices so the farmer have motivations to canges to progress gading coconut on simalidu koto salak damasraya general achieve because high gading coconut on the farmer hope economy moun from before now. 3) also, because the farmer more easy to organize it on simalidu koto salak damasraya general achieve because simple prepation cultivation gading coconut comparation wet rice fiel plant.